Cadmium Doped Copper Containing Phosphate Glass as a Bandpass Filter for Solar Cell Protection - Abd El-Ghany, Hytham Ahmed (JOURNAL OF ADVANCES IN PHYSICS, 2018)
A glass system of composition 44P2O5-38ZnO-2CuO-(16-x)Na2O-xCdO (where, x = 1, 2, 3, 4, and 5 mol%) has been prepared using the conventional melt quenching technique. XRD patterns confirmed the amorphous nature for the prepared samples. Archimedes method was used to determine the density of the prepared glass samples then the molar volume was calculated. The optical spectroscopic investigations of the prepared glass samples were carried out over the spectral range (190-1100 nm). The transmission spectra revealed that the prepared glass samples behave as bandpass filters in the visible region. The absorption studies were employed to determine the optical band gap and Urbach energy. The spectral distribution of the refractive index assured the lowest dispersion of the glass in the visible region. Other physical parameters such as the extinction coefficient, the optical conductivity, and the complex dielectric constant were evaluated. The results suggested the practicality of employing such low-cost glass as a bandpass filter for optical applications such as UV-elimination and solar cell protection. The role of CdO as a network modifier in the phosphate glass was revealed.